👤

Va rog sa ma ajutati .Fie functia f(x) = 5x -1.Demonstrati ca f(11 supra 7 ) - f( 4 supra 7 ) = f( 13 supra 9 ) - f( 4 supra 9 )

Răspuns :

f([tex] \frac{11}{7} [/tex]) = [tex] \frac{55}{7} [/tex] -1 = [tex] \frac{48}{7} [/tex]
f( [tex] \frac{4}{7} [/tex]) = [tex] \frac{20}{7} [/tex] -1 = [tex] \frac{13}{7} [/tex]
f( [tex] \frac{13}{9} [/tex]) = [tex] \frac{65}{9} [/tex] -1 = [tex] \frac{56}{9} [/tex]
f( [tex] \frac{4}{9} [/tex]) = [tex] \frac{20}{9} [/tex] -1 = [tex] \frac{11}{9} [/tex]

[tex] \frac{48}{7} [/tex] -  [tex] \frac{13}{7} [/tex] =  [tex] \frac{56}{9} [/tex] -  [tex] \frac{11}{9} [/tex]
[tex] \frac{35}{7} [/tex] =  [tex] \frac{45}{9} [/tex] 
5 = 5